Faktor- Faktor Yang Mempengaruhi Tingkat Kesadaran Pekerja dalam Menggunakan Alat Pelindung Diri (Studi Kasus :Pembangunanturning Area. Pertambangan Batu Bara Pt.Mifa Bersaudara. Kecamatan Meurebo, Kabupaten Aceh Barat) - Dian Febrianti; Inseun Yuri Salena (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2020)
Personal protective equipment (PPE) is a device used by workers to protect themselves from potential hazards and workplace accidents that may occur at work. The use of PPE by workers is an attempt to avoid exposure to the risk of hazards in the workplace. Occupational Safety and Health problems in Indonesia are still often ignored. The high number of work accidents indicates this. This study aims to identify the dominant frequency of workers' level of awareness using PPE and to find out a significant level of awareness of age, work tenure and education factors that affect the level of awareness of workers using personal protective equipment. This research located in coal mining, PT Mifa Bersaudara, Meurebo District, West Aceh Regency. The data used in this study were observation and questionnaire distribution, processed using SPSS software with Univariate and bivariate methods which are to determine the dominant factor and significant relationship to the level of awareness of workers in using personal protective equipment. Based on the results of the study, workers who dominated based on the age of workers, aged 20-30 years were 21 people with a percentage of the number of workers reaching 48.8%, and at least 41-50 years of age were 9 (nine) people with 14%. Whereas based on years of service, the average working period of the employees is mostly 4-7 Years with 58.1%. Based on education, the level of junior high school education is very dominant, up to 19 people with 44.2%, so based on the results of the study it is necessary to conduct learning in fulfilling the obligation to use PPE in the form of training and socialization of procedures and instructions for the use of Personal Protective Equipment for workers to prevent work accidents and for the occupational health and safety.